Great exaggerations! Death of libraries - CRIBB, Gulcin (Institutional Knowledge at Singapore Management University, 2018)
Libraries these days are built digital brick by digital brick – brick being the metaphor for digital books, journals, articles, objects, media, digital infrastructure, networks, apps, data, and analytics. The growth of print collections has been declining considerably in recent times. Singapore Management University (SMU) Libraries spends over 90% of its funds on digital collections, 80% of its collections are digital.